Systematic literature review: police and personality traits / Norlida Zakirai@Zakaria … [et al.] - Zakirai@Zakaria, Norlida; Osman, Idris; Mohd. Jidi, Munirah; Jamian, Nur Faithzah; Noranee, Shereen (2023)
The police force stands as the central institution within the framework of the criminal justice system. Possessing extensive authority unlike any other official or governmental entity, they play an indispensable role in upholding the legal system. Policing, as a profession, presents numerous challenges due to the constant pressures and stresses inherent in the work environment. Consequently, scholars have turned their attention to conducting research within the context of law enforcement. Thus, this paper aims to examine what recent output is associated with a study on personality traits in the policing context. Employing the Preferred Reporting Items for Systematic Review and Meta-Analyses (PRISMA) methodology, this study examined prevailing trends and patterns in literature that aligned with its research objectives. To locate high-quality literature published between 2018 and 2023, reputable databases, Scopus and Web of Science were utilized. The findings of this study have significant implications for future research, shedding light on the impact of personality traits on not only the police profession but also other law enforcement agencies.